2014
DOI: 10.3329/jsr.v6i2.17590
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Synthesis of Some Novel Spiro Heterocycles Related to Indoline Moiety

Abstract: Reactions of indole-2,3-dione 1 with 2-mercaptobenzimidazole, o-phenylenediamine, 2-aminophenol, 2-aminobenzothiazole, 2-aminobenzimidazole and 3-methyl-1-phenyl-2-pyrazolin-5-one were carried out to give compounds spiroindolethiazetobenzimidazole 2, spirobenzimidazole(oxazole)indoline 3a,b, benzothiazol(imidazol) iminoindolinone 4a,b and methyloxoindolylidenepyrazolone 5 respectively. Compound 5 was reacted with 2-aminophenol as well as o-phenylenediamine to give new spirooxazepine and diazepine derivatives 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…[8][9][10] Moreover, pyrazole derivatives revealed many practical applications in the medicinal field as antioxidant, antidepressant, anti-influenza, anticancer activities. [11][12][13][14][15][16][17][18] In continuation of our work on pyrazolidinediones, [19][20][21][22][23][24] we report herein green synthetic investigation of some spiroheterocycles of potential biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Moreover, pyrazole derivatives revealed many practical applications in the medicinal field as antioxidant, antidepressant, anti-influenza, anticancer activities. [11][12][13][14][15][16][17][18] In continuation of our work on pyrazolidinediones, [19][20][21][22][23][24] we report herein green synthetic investigation of some spiroheterocycles of potential biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Isatin has recently been used as a reagent due to its various biological (anxiogenic, sedative, anticonvulsant, endogenous MAO inhibitor and potent antagonist on atrial natriuretic peptide receptor) and structural functional properties [1,[5][6][7][8]. One of the most frequently used reactions in this context is the Schiff base reaction [9,10]. Schiff bases are used as a substrat in different cyclization or replacement reactions were synthesized using different aldehyde and amine derivatives (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…Table 4 obviously demonstrates that DCDBTSD is effective catalysts in terms of reaction time and yield of obtained product relative to other reported catalysts. 30 It has been reported that the spiro-oxindole heterocyclic framework is an important structural motif in biologically relevant compounds as natural products and pharmaceuticals, e.g., surugatoxin, horsfiline, spirotryprostatin A and B, elacomine, gelsemine, alstonisine and strychnofoline. 30 It has been reported that the spiro-oxindole heterocyclic framework is an important structural motif in biologically relevant compounds as natural products and pharmaceuticals, e.g., surugatoxin, horsfiline, spirotryprostatin A and B, elacomine, gelsemine, alstonisine and strychnofoline.…”
Section: Introductionmentioning
confidence: 99%